A qualitative assessment of behavioral interview method among anesthesiology residency applicants - Sujatha Ramachandran; Angela Vick; Singh Nair; Sarang Koushik; Ludovica Stilli; Kateryna Slinchenkova; Omar Viswanath; Karina Gritsenko; Naum Shaparin (Health Psychology Research)
# Background